Kinetic Study of Thermal Pyrolysis of Polypropylene Waste from North Refineries Company - Hamd, Marwan I.; Akream, Nuha S.; Gheni, Saba A. (Journal of Petroleum Research and Studies, 2025)
The process of pyrolysis is the thermal degradation of plastic waste in the absence of oxygen at high temperatures, which leads to the decomposition of the material to form a mixture of gases, liquids, and some solid residues. To investigate the pattern of degradation that occurs in the plastic materials when subjected to the reaction conditions that would be employed for pyrolysis, thermal gravitational analysis studies were conducted. Consequently, the TGA analysis was conducted at a moderate reaction temperature of 900 °C for a duration of 30 minutes while being agitated with nitrogen flow. The objective of the experiment was to predict the plastic’s weight reduction over time and temperature. The process included heating about 10 mg of the polypropylene (in nitrogen) at a rate of 5 °C min-1 to a final temperature of 900 °C. The sample spent thirty minutes at that temperature. The goal of this investigation was to construct a polypropylene thermal model for the production of green fuel. In the present work, a kinetic model was developed for the thermal degradation of North Refineries Company polypropylene plastic waste via TGA data obtained at no-isothermal conditions. The TGA data was coupled with the Arrhenius equation to find the thermal degradation kinetics. Different models were examined to figure out the most suitable model that fits the thermal degradation kinetics and it was found that the Coats-Redfern model is the one that fits the mechanism of thermal degradation of the waste. The predicted activation energy and pre-exponential factor obtained from analysis of the kinetics data based on the Coats-Redfern model were 128.74 kJ/mol and 2.603. The value of the activation energy for polypropylene indicates within average values of the activation energy in other literature, in agreement with other similar literature reports.